Emergence of long-range angular correlations in low-multiplicity proton-proton Collisions - Acharya, Shreyasi (2024)
This Letter presents the measurement of near-side associated per-trigger yields, denoted ridge yields, from the analysis of angular correlations of charged hadrons in proton-proton collisions at √=13  TeV. Long-range ridge yields are extracted for pairs of charged particles with a pseudorapidity difference of 1.4<|Δ⁢|<1.8 and a transverse momentum of 1<T<2  GeV/, as a function of the charged-particle multiplicity measured at midrapidity. This Letter extends the measurements of the ridge yield to the low multiplicity region, where in hadronic collisions it is typically conjectured that a strongly interacting medium is unlikely to be formed. The precision of the new low multiplicity results allows for the first direct quantitative comparison with the results obtained in e+⁢e− collisions at √=91  GeV and √=183–209  GeV, where initial-state effects such as preequilibrium dynamics and collision geometry are not expected to play a role. In the multiplicity range 8≲⟨ch⟩≲24 where the e+⁢e− results have good precision, the measured ridge yields in ⁢ collisions are substantially larger than the limits set in e+⁢e− annihilations. Consequently, the findings presented in this Letter suggest that the processes involved in e+⁢e− annihilations do not contribute significantly to the emergence of long-range correlations in ⁢ collisions.